O uso de Controladores Fuzzy Adaptativos, implementados em microcontroladores, no controle de vibrações de sistemas mecânicos - Nuñez, Israel Jorge Cárdenas (2001)
This work deals with the active control of vibrations in dynamic systems. This area of mechanical engineering is one in which the technological progress represented by the development of new materials, new sensors and actuators and new control technologies open interesting and challenging possibilities. In the control area, the heuristic formulation and the short development cycle has been promoting significant progress to fuzzy control technology. These controllers do not need mathematical models of the involved systems to operate. A classic fuzzy controller project demands a priori, the knowledge of an expert about the system behavior. In the attempt to overcome this demand, in the last years, adaptive fuzzy controllers were developed. A review of such controllers as well as a new adaptation mechanism that modifies the fuzzy controller gains are presented in this work. The nature of this mechanism is fuzzy and it operates on line and in parallel whit the fuzzy controller. Another reason for the experienced success of fuzzy controllers is the easiness of implementation of this technology in microcontrollers of low cost. A brief review about microcontrollers is presented. In order to evaluate experimentally the proposed control methodology and in the perspective of accumulating experience in the use of piezoelectric materials as actuators/sensors, as well as the microcontrollers employment, this work presents and discusses two applications of vibration control: the first one involves a vibratory system controlled by electromagnetic actuators and, the second is a flexible beam in which accelerometers are used as motion sensors and electromagnetic actuators are used for control purposes. Finally, a discussion of the obtained experimental results is presented and the control methodology proposed is evaluated. Some future developments using the techniques presented are promoted to conclude the present contribution